THE LEGAL IMPLICATIONS ON THE VIOLATION OF THE LEGALITY COSMETICS BUSINESS - Siagian, Mai Irwana Br.; Simatupang, Esra Elika; Dhaki, Pianus (Lembaga Riset dan Pengembangan Sumatera Utara, 2025)
This study aims to analyze the legality of the cosmetic business in Indonesia with a focus on cases of illegal cosmetics circulating without permission from the Food and Drug Supervisory Agency (BPOM). Cosmetic businesses that do not comply with regulations have a high risk to consumer health and create unfair business competition. In this study, a normative legal research method with a qualitative descriptive approach is used to understand how cosmetic business regulations are applied and their legal implications for business actors. The results of the study show that existing regulations, such as Law Number 8 of 1999 concerning Consumer Protection, Law Number 7 of 2014 concerning Trade, and Regulation of the Food and Drug Supervisory Agency (BPOM) Number 12 of 2023 concerning Technical Requirements for Cosmetic Products, have clearly regulated the legality of cosmetic products. This study also highlights that supervision of cosmetic products is carried out in two stages, namely supervision before circulation (Pre-Market) and supervision after circulation (Post-Market). Although the Food and Drug Supervisory Agency (BPOM) has a mechanism to control product safety, there are still challenges in ensuring business actors' compliance with applicable regulations. Therefore, a more effective strategy is needed to improve consumer education and strengthen supervision of illegal cosmetic businesses.